The Foundation of the Origin of Species Two Essays Written in 1842 and 1844 by Charles Darwin - Darwin, Charles 1809-1882 (Cambridge University Press, 1909)
The development of Charles Darwin's views on evolution by natural selection has fascinated biologists since the 1859 publication of his landmark text On The Origin of Species. His experiences, observations and reflections during and after his pivotal journey on the Beagle during 1831–36 were of critical importance. Darwin was not, however, a man to be rushed. While his autobiography claims that the framework of his theory was laid down by 1839, its first outline sketch did not emerge until 1842. That essay was heavily edited, with many insertions and erasures. It formed the vital kernel of his more expansive but also unpolished and unpublished essay of 1844. Following careful editing by his son Francis, both essays were published in 1909, and are reproduced here. Reading these side by side, and together with the Origin, permits us to scrutinise selection and evolution truly in action
Title from publisher's bibliographic system (viewed on 05 Oct 2015)